Integrasi Teknologi Dalam Evaluasi Pendidikan Islam: Studi Literatur Tentang E-Assessment Dan Big Data - Syarif, Jamal; Huda, Nuril; Hermina, Dina (Jurnal Evaluasi Pendidikan, 2024)
This study examines the role of technology, such as e-assessment, online platforms, and big data, in supporting the evaluation process in Islamic education in the digital era. Using a systematic literature review method, the research identifies key challenges, including digital gaps and resource limitations in schools and madrasas. The findings reveal that e-assessment and online platforms enhance evaluation efficiency and accessibility, while big data analysis provides in-depth insights into students’ cognitive, affective, and psychomotor development. However, significant challenges persist, particularly in aligning these technologies with Islamic educational principles and addressing digital disparities. To overcome these obstacles, the study proposes solutions, such as capacity-building programs for educators, developing inclusive technology infrastructure, and creating guidelines to ensure Islamic values are embedded in evaluation practices. This research contributes to advancing Islamic education by integrating technology while maintaining its spiritual and ethical dimensions.